PENGARUH ISLAMIC BRANDING, PELAYANAN SYARIAH, PHISICAL ENVIRONMENT TERHADAP CORPORATE IMAGE (STUDI KASUS PADA NASABAH BANK SYARIAH KOTA SEMARANG) - Fajar Adhitya (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This research aims to examine the influence of the Islamic Branding, Sharia Services, and physical environment on the corporate image of Islamic banking in Semarang. This study uses quantitative research approach with primary data source. The research population included the customers of Islamic Banking in Semarang. The sampling method uses purposive technique which involving 100 respondents. The data used in this study were collected by distributing questionnaires to the respondents. The analysis techniques used in this study is multiple linear regression models that were processed using SPSS program. Based on the results of statistical tests obtainedthe Islamic Branding, Sharia Services, and Physical Environment affect the Corporate Image. This concludes that the corporate image variable can be explained by the Islamic Branding, Sharia Services, and Physical Environment while the rest is affected by other variable which do not included in this research. In other words, the first hypothesis (H1), the second hypothesis (H2), and the third hypothesis (H3) are all accepted. Penelitian ini bertujuan untuk menguji seberapa besar pengaruh Islamic branding, pelayanan syariah, dan physical environment terhadap corporate image Bank Syariah di Kota Semarang. Penelitian ini merupakan jenis penelitian kuantitatif dan sumber data primer. Populasi penelitian ini adalah nasabah Bank Syariah di Kota Semarang. Metode pengambilan sampel menggunakan purposive sampling yang melibatkan sebanyak 100 responden. Pengumpulan data dilakukan melalui pembagian kuesioner kepada para responden. Teknik analisis data dengan menggunakan uji regresi linier berganda dengan program SPSS. Berdasarkan hasil uji statistik diperoleh hasil Islamic branding, pelayanan syariah, dan physical environment berpengaruh terhadap corporate image. Hal ini berarti variabel corporate image dapat dijelaskan oleh Islamic branding, pengetahuan syariah, dan physical environment dan sisanya dipengaruhi variabel lain di luar penelitian ini. Dengan kata lain, hipotesis pertama (H1), hipotesis kedua (H2), dan hipotesis ketiga (H3) diterima.